2011
DOI: 10.1007/s11618-011-0186-3
|View full text |Cite
|
Sign up to set email alerts
|

12 From birth to early child care

Abstract: The birth cohort study of the German National Educational Panel Study takes up the challenge of measuring education-relevant conditions and processes as well as the development of competencies in the first years of a child's life. The rationale to begin "from the crib on" can be found in results of infant and early childhood research. We review the design and main features of existing birth cohort studies in the field of education conducted in developed countries. Most studies begin when infants are between 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Zur Erfassung der familiären Lernumwelt in der frühen Kindheit und deren Auswirkungen auf die weitere Bildung wurden im Rahmen des Nationalen Bildungspanels (NEPS) seit 2011 videografierte Eltern-Kind-Interaktionen einer national repräsentativen Stichprobe (n = 3.481) untersucht [29][30][31]. Messungen der Eltern-Kind-Interaktion wurden zu drei Messzeitpunkten (7, 16 und 26 Monaten) durchgeführt.…”
Section: Eltern-kind-interaktions Einschätzskala (Ekie)unclassified
“…Zur Erfassung der familiären Lernumwelt in der frühen Kindheit und deren Auswirkungen auf die weitere Bildung wurden im Rahmen des Nationalen Bildungspanels (NEPS) seit 2011 videografierte Eltern-Kind-Interaktionen einer national repräsentativen Stichprobe (n = 3.481) untersucht [29][30][31]. Messungen der Eltern-Kind-Interaktion wurden zu drei Messzeitpunkten (7, 16 und 26 Monaten) durchgeführt.…”
Section: Eltern-kind-interaktions Einschätzskala (Ekie)unclassified
“…If newborn cohort studies took direct measures into consideration in addition to interviews and questionnaires, they often relied on the Bayley Scales of Infant Development (Bayley 2006;Schlesiger et al 2011 for a brief overview). However, the NEPS feasibility and pilot studies revealed that the standardized administration of test items (using an educationally sound selection of items) turned out to be highly error-prone for trained interviewers who are usually experts in administering interviews but not tests.…”
Section: Selecting and Measuring Relevant And Predictive Indicators Omentioning
confidence: 99%
“…However, it is discussed whether the changes in the psychomotor development are due to violence that took place before the sheltering, or on the contrary, are originated by prolonged sheltering, and whether these places would certainly remain as keepers of this delay (Van Ijzendoorn et al, 2011;Tizard & Tizard, 1967;Tizard & Joseph, 1970;Siqueira & Dell'Aglio, 2006;Manso, Garcia-Baamonde, & Alonso, 2011). Nonetheless, other studies state that without detection and intervention, when necessary, this scenery may lead to future problems in older ages, as the rising of other incapabilities, for example those presented at school related to difficulties in essential areas for learning (Schlesiger et al, 2011;Conti et al, 2012;Cardona, Manes, Escobar, López, & Ibáñez, 2012).…”
Section: Introductionmentioning
confidence: 99%